Histological changes in endometrium during follicular and luteal phases in water buffalo (Bubalus bubalis) - ALBOGHOBEISH, N (The Indian Journal of Animal Sciences, 2013)
Sections of endometrium of 20 healthy water buffaloes (3-5 year-old) during follicular and luteal phases revealed an increaSe in the height and secretory activity of epithelial cells during the luteal phase. Cyclic erosion of the surfac epitheLum was seen in curly dioestrus. The extravosation of blood, necrosis and de-epithilization as well as edema in the stroma of endometrium were observed during the follicular phase. The branched tubular endometrial glands were not seen in the caruncular area. The number of tile superficial glands were more during luteal phase (69.8±8.1 glands/mm2)(han during follicular phase (53.6±7.8 glands/mm2). The diameter of the glands at follicular phase (54.8±6.9) increased during the luteal phase (85.±8.6mu).